2017
DOI: 10.1017/s000711451700215x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of effects of dietary arachidonic acid and EPA on growth, tissue fatty acid composition, antioxidant response and lipid metabolism in juvenile grass carp,Ctenopharyngodon idellus

Abstract: Four isonitrogenous and isoenergetic purified diets containing free arachidonic acid (ARA) or EPA (control group), 0·30 % ARA, 0·30 % EPA and 0·30 % ARA+EPA (equivalent) were designed to feed juvenile grass carp (10·21 (sd 0·10) g) for 10 weeks. Only the EPA group presented better growth performance compared with the control group (P<0·05). Dietary ARA and EPA were incorporated into polar lipids more than non-polar lipids in hepatopancreas but not intraperitoneal fat (IPF) tissue. Fish fed ARA and EPA showed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 62 publications
3
25
0
Order By: Relevance
“…In the present study, the contents of MDA both in haemolymph and hepatopancreas increased as dietary lipid increased from 5•8 to 15•1 %, indicating that lipid peroxidation products increased with increased dietary lipid level, possibly reflecting higher n-3 LC-PUFA levels. Overall, these results demonstrated that relatively high dietary lipid levels led to an increased risk of peroxidation and imposed a peroxidation burden (36,37) .…”
Section: Discussionmentioning
confidence: 72%
“…In the present study, the contents of MDA both in haemolymph and hepatopancreas increased as dietary lipid increased from 5•8 to 15•1 %, indicating that lipid peroxidation products increased with increased dietary lipid level, possibly reflecting higher n-3 LC-PUFA levels. Overall, these results demonstrated that relatively high dietary lipid levels led to an increased risk of peroxidation and imposed a peroxidation burden (36,37) .…”
Section: Discussionmentioning
confidence: 72%
“…At the end of the feeding trial, the fish were fasted for 24 hr and anaesthetized with tricaine methanesulfonate (MS222; 0.06 g/L; Tian et al, ). The body weights, lengths (18 fish/tank) and hepatopancreas weights of the fish (12 fish/tank) were measured to calculate their condition factors and hepatosomatic index.…”
Section: Methodsmentioning
confidence: 99%
“…At the end of the feeding trial, the fish were fasted for 24 hr and anaesthetized with tricaine methanesulfonate (MS222; 0.06 g/L; Tian et al, 2017…”
Section: Sampling Proceduresmentioning
confidence: 99%
“…Afterward, 5-µm sections were cut with a rotary microtome (RM2235, Leica, Germany), mounted on glass slides, and stained with H&E. Histological samples were observed and photographed using an upright microscope (Leica biosystems, Wetzlar, Germany). The average myocyte size per image was quantified using Photoshop (Adobe) as previously described (Tian et al, 2017). An average value across three non-overlapping images (three/section) was calculated for each group.…”
Section: Hematoxylin and Eosin (Hande) Muscle Stainingmentioning
confidence: 99%